UPAYA GURU DALAM MENINGKATKAN KUALITAS HAFALAN Al-QUR'AN PADA SANTRI PONDOK PESANTREN DAARUL RIYADHOH AR-ROSYADY - Nunik Syifa Fauziah; Fahmi Irfani; Kamalludin Kamalludin (KOLONI, 2022)
The process of implementing memorizing the Qur'an by students in Islamic boarding schools includes several methods of memorizing. The guidance of a teacher is also very important in the process of memorizing the Al-Qur'an to correct and straighten the recitation of the Al-Qur'an both in terms of makhraj, as well as the length of the short reading. Al-Qur'an memorization lessons at Daarul Riyadhoh Ar-Rosyady Islamic Boarding School, Cimanggu Pabuaran, Bogor City, are an additional program that is carried out at salafiyah Islamic boarding schools. The purpose of this study is to find out the efforts and methods used by the teacher to improve the quality of memorizing the Qur'an as well as the supporting and inhibiting factors in the process of memorizing the Qur'an for students at Daarul Riyadhoh Ar-Rosyady Islamic Boarding School. The method used in this research is descriptive qualitative, the steps in this research are collecting data, analyzing and developing conceptual. Collecting data in this descriptive qualitative research using observation, interview, and documentation methods. The conclusion from this study is that the efforts made by the teacher in improving the quality of memorizing the Qur'an consist of: Providing motivation, correcting readings, creating a pleasant learning atmosphere, providing rewards and punishments, guiding muraja'ah and using various methods, different methods. teachers apply in improving the quality of Al-Qur'an memorization, namely: the wahdah method, the kitabah method, the jama' method, the talaqqi method, and sima'an Al-Qur'an, supporting factors in improving the quality of Al-Qur'an memorization: emotional students, the appropriate method, and the motivation given by the teacher, as for the obstacles in memorizing the Qur'an, namely: There are students who have not been able to read the Al-Qur'an, lack of motivation, and a feeling of laziness. Keywords: teacher's efforts, quality of memorizing the Qur'an.